"Volume-point" mass transfer constructal optimization based on flow resistance minimization with cylindrical element. (October 2015) - Chen, Lingen; Feng, Huijun; Xie, Zhihui; Sun, Fengrui
Highlights: A mass transfer model with cylindrical porous media is investigated. Constructal optimization of the model is carried out. Minimum dimensionless maximum pressure drop is taking as optimization objective. Optimal constructs of cylindrical element and first order assembly are obtained. Constructal optimization of cylindrical assembly chases for reduction of limit pressure in assembly. Abstract: Analogizing with Alebrahim and Bejan's (Alebrahim and Bejan, 1999) heat conduction model of a cylindrical assembly, a mass transfer model with cylindrical porous media is investigated in this paper. Constructal optimizations of the cylindrical element and first order assembly are carried out by taking minimum dimensionless maximum pressure drop (i.e., minimum dimensionless flow resistance with the specified total mass flow rate) as optimization objective and using analytical solution method. The results show that there exist optimal ratios of the internal and external parameters which lead to twice minimum dimensionless maximum pressure drops of the cylinders. Different from Alebrahim and Bejan's cylindrical heat conduction model, there are three kinds of permeability materials in the cylindrical mass transfer model, and different parameters have different effects on the optimal constructs of the models. The constructal optimization of the model based on the minimization of dimensionless maximum pressure drop chases for the reduction of the limit pressure in the assembly, and its mass transfer performance can be improved simultaneously.